2021
DOI: 10.3390/jcm10132886
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Kidney Disease in Patients with Diabetes in Extremadura (Spain) during the Years 2012, 2013 and 2014: An Observational Study

Abstract: Diabetes mellitus (DM) is one of the leading causes of chronic kidney disease (CKD). We analyzed the prevalence of CKD in the population with diabetes in Extremadura (Spain). retrospective observational study was carried in the diabetic population attended in the Extremadura Health System in 2012–2014. A total of 38,253 patients, ≥18 years old were included. Estimated glomerular filtration rate (eGFR) was calculated using the CKD Epidemiology Collaboration equation. CKD was defined as follow: an eGFR <60 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This is the first study to develop a nomogram to predict PAH in patients with CKD, and we found that age, DM, Hb, PLT count, Scr, LVDd, LAD, MPAD, and LVEF were independent risk factors for PAH. The prevalence of CKD increases with age, and renal function gradually decreases so that 34.0% of people ≥ 65 years old have stage 3 or above CKD [21], which may be related to elderly individuals being more prone to chronic diseases such as hypertension, diabetes, and coronary heart disease. An epidemiological study showed that the prevalence of CKD in elderly individuals over 70 years old reached 47% [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to develop a nomogram to predict PAH in patients with CKD, and we found that age, DM, Hb, PLT count, Scr, LVDd, LAD, MPAD, and LVEF were independent risk factors for PAH. The prevalence of CKD increases with age, and renal function gradually decreases so that 34.0% of people ≥ 65 years old have stage 3 or above CKD [21], which may be related to elderly individuals being more prone to chronic diseases such as hypertension, diabetes, and coronary heart disease. An epidemiological study showed that the prevalence of CKD in elderly individuals over 70 years old reached 47% [22].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CKD increases with age, and renal function gradually decreases so that 34.0% of people ≥ 65 years old have stage 3 or above CKD [ 21 ], which may be related to elderly individuals being more prone to chronic diseases such as hypertension, diabetes, and coronary heart disease. An epidemiological study showed that the prevalence of CKD in elderly individuals over 70 years old reached 47% [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic kidney disease is defined as persistent albuminuria (an albumin‐to‐creatinine ratio >3 mg/mmol), a persistently reduced renal function (an estimated glomerular filtration rate <60 mL/min per 1.73 m 2 ) or both for greater than 3 months 5 . The prevalence of DKD in people with diabetes varies depending on the cohort in the study, the population from which the sample was derived and the region studied: 42% (all types of diabetes, secondary care) in Ireland 6 , 32% (type 1 diabetes), and 42% (type 2 diabetes) in the UK (primary and secondary care) 7 , 25% (all types of diabetes, pharmacy, and clinical records) in Spain 8 , 47% (type 2 diabetes based on medication claims from insurance databases) in France 9 , and 24% (type 1 diabetes, secondary care) in Italy 10 . Risk factors for DKD include genetic determinants but also modifiable risk factors including hypertension, dyslipidemia, hyperglycemia, and smoking 10 .…”
Section: Introductionmentioning
confidence: 99%